Cellulose ester derivative modified alumina, and preparation method and application thereof
Patent Information
- Application Number
- CN202610992370.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-06
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2046-07-06
AI Technical Summary
但在部分高性能应用,如需提升胶剂粘接性能的应用中,该手段需使用成本较高的偶联剂,如钛酸酯偶联剂等对粉体进行改性,且为达到一定效果,改性粉体的添加质量分数较低,难以起到其提升、改善胶体韧性等其他作用
[0024]本发明提供了一种纤维素酯化衍生物改性氧化铝,其中,纤维素酯化衍生物由纤维素中的羟基与有机酸溶液中的羧基发生酯化反应而得到。进一步,所述纤维素酯化衍生物可与氧化铝粉体表面的羟基完成接枝反应,从而在氧化铝的表面形成高分子层,增加无机氧化铝粉体与硅油的界面相容性。因此,以纤维素酯化衍生物改性氧化铝作为填料,制备有机硅橡胶胶料,可提升其机械性能、韧性和热稳定性等,进一步提升了材料的应用面,且相对现有的改性材料,纤维素具有环境友好的特点,更符合如今环保、可持续发展的现代工业需求。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of potting compound technology, specifically relating to a cellulose esterified derivative modified alumina, its preparation method, and its application. Background Technology
[0002] Alumina powder, as a thermally conductive filler with advantages such as high hardness, high strength, and excellent thermal stability, is often used in thermally conductive potting compounds to improve the thermal conductivity of the compound and reduce production costs. Generally, as a filler, alumina should be uniformly dispersed to achieve the best effect. However, in conventional silicone oil / silicone resin and thermally conductive filler mixtures in potting compounds, the density difference between the filler and silicone oil is significant, and alumina powder, being highly polar, cannot fully integrate with organic media. Furthermore, with prolonged standing time, it is prone to agglomeration, oil-powder separation, and sedimentation. Therefore, improving the oleophilicity of alumina powder surface or enhancing its compatibility and dispersibility in polymer matrices is crucial.
[0003] Existing technologies typically use silanes or coupling agents to effectively chemically modify the surface of alumina powder through a series of reactions. Silane hydrolysis produces silanols, which, under heating conditions, undergo dehydration condensation and self-polymerization with the hydroxyl groups on the alumina surface, ultimately grafting onto the surface and introducing non-polar lipophilic groups. Studies show that the modified powder exhibits good wettability in resins, low interfacial tension with the resin, easy and uniform dispersion, and reduced particle aggregation, thus enhancing the colloid's anti-settling properties. However, in some high-performance applications, such as those requiring improved adhesive bonding performance, this method necessitates the use of expensive coupling agents, such as titanate coupling agents, to modify the powder. Furthermore, to achieve sufficient effect, the added mass fraction of modified powder is relatively low, making it difficult to achieve other benefits such as improving colloid toughness. Therefore, a new alumina modification scheme is needed to expand its application in organosilicon resin systems and overcome its limitations. Summary of the Invention
[0004] In view of this, the purpose of this invention is to provide a cellulose esterified derivative-modified alumina, its preparation method, and its application. The cellulose esterified derivative-modified alumina exhibits good compatibility with various silicone resin systems.
[0005] To achieve this objective, the present invention adopts the following technical solution:
[0006] In a first aspect, the present invention provides a cellulose esterified derivative modified alumina, which is obtained by reacting a cellulose esterified derivative with alumina.
[0007] The cellulose esterified derivative is obtained by reacting cellulose with an organic acid solution.
[0008] Preferably, the ratio of cellulose to organic acid solution is 1 g:(40~60) mL, and the mass ratio of cellulose to alumina is 1:(1.0~2.5).
[0009] Preferably, the cellulose is selected from microcrystalline cellulose.
[0010] Preferably, the purity of the microcrystalline cellulose is above 90%.
[0011] Preferably, the organic acid solution is an aqueous solution of organic acid with a mass fraction of 50-70%.
[0012] Preferably, the organic acid in the organic acid solution is selected from any one or more of formic acid, acetic acid, or propionic acid.
[0013] Preferably, the alumina has a medium particle size of 20~70 μm.
[0014] Secondly, the present invention provides a method for preparing the above-mentioned cellulose esterified derivative modified alumina, which includes the following steps:
[0015] S1: Reaction of cellulose with organic acid solution yields cellulose esterification derivatives;
[0016] S2: Mix and react cellulose esterified derivatives with alumina to obtain cellulose esterified derivative modified alumina.
[0017] Preferably, the reaction in step S1 is carried out under stirring conditions, the reaction temperature is 50~80℃, and the reaction time is 2~4 h.
[0018] Preferably, the reaction in step S2 is carried out under stirring conditions, the reaction temperature is 50~80℃, and the reaction time is 2~10 h.
[0019] Preferably, the esterification reaction in step S2 is carried out in the presence of concentrated sulfuric acid. After the esterification reaction is completed, an alkaline substance is used for neutralization. Preferably, sodium carbonate and / or potassium carbonate are used for neutralization.
[0020] Thirdly, the present invention provides an application of the above-mentioned cellulose esterification derivative modified alumina in organosilicon rubber compounds.
[0021] Fourthly, the present invention provides an organosilicon rubber compound comprising the aforementioned cellulose esterified derivative modified alumina, silicone oil, and additives.
[0022] Preferably, the cellulose esterified derivative modified alumina accounts for 30-70 wt% of the organosilicon rubber compound.
[0023] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0024] This invention provides a cellulose esterified derivative-modified alumina, wherein the cellulose esterified derivative is obtained by esterification of hydroxyl groups in cellulose with carboxyl groups in an organic acid solution. Furthermore, the cellulose esterified derivative can undergo a grafting reaction with hydroxyl groups on the surface of alumina powder, thereby forming a polymer layer on the surface of the alumina and increasing the interfacial compatibility between the inorganic alumina powder and silicone oil. Therefore, using cellulose esterified derivative-modified alumina as a filler to prepare organosilicon rubber compounds can improve its mechanical properties, toughness, and thermal stability, further expanding the application range of the material. Compared with existing modified materials, cellulose has environmentally friendly characteristics, which better meet the needs of modern industry for environmental protection and sustainable development. Detailed Implementation
[0025] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0026] This invention provides a cellulose esterified derivative modified alumina, which is obtained by reacting a cellulose esterified derivative with alumina.
[0027] In this invention, the cellulose esterified derivative is preferably obtained by reacting cellulose with an organic acid solution.
[0028] Natural cellulose molecules, as natural polymers, contain a large number of hydroxyl groups and other polar groups in their structure. However, if cellulose is directly used as a surface modifier for alumina, it is difficult to form sufficient bonds on the surface of alumina particles, thus hindering the effective improvement of powder properties. Therefore, this invention employs a pre-chemical modification method to partially hydrolyze cellulose. Specifically, cellulose molecules undergo esterification with an organic acid solution in a specific organic system. Under certain catalytic conditions, some hydroxyl groups on the cellulose molecular chain can be converted into ester groups through the esterification reaction.
[0029] Specifically, in some embodiments of the present invention, the present invention uses a certain proportion of organic acid aqueous solution to stir the reaction at a certain temperature to pre-activate and swell the structure of cellulose molecules, which can also more effectively complete the subsequent esterification and modification reactions. The ratio of cellulose to organic acid solution is 1 g:(40~60) mL, such as 1 g:40 mL, 1 g:42 mL, 1 g:45 mL, 1 g:48 mL, 1 g:50 mL, 1 g:52 mL, 1 g:55 mL, 1 g:58 mL, or 1 g:60 mL, etc. The organic acid in the organic acid aqueous solution is selected from any one or more of formic acid, acetic acid, or propionic acid, and the mass fraction of the organic acid is 50~70%, such as 50%, 52%, 55%, 58%, 60%, 62%, 65%, 68%, or 70%, etc. In some embodiments of the present invention, an acetic acid aqueous solution with a mass fraction of 50~70% is preferably used.
[0030] In this invention, the above reaction is preferably carried out under the condition of concentrated sulfuric acid, which is used to initiate the esterification reaction and to provide an acidic environment for better hydrolysis of cellulose. After the reaction is completed, an alkaline substance is preferably added for neutralization. The alkaline substance is preferably sodium carbonate and / or potassium carbonate. Preferably, the weight ratio of concentrated sulfuric acid to alkaline substance is 1:1.3 to 1:1.5, such as 1:1.3, 1:1.35, 1:1.4, 1:1.45 or 1:1.5.
[0031] In some embodiments of the present invention, a certain amount of organic acid aqueous solution is preferably added to toluene and heated at 40-60°C, preferably 50°C, for 1-3 hours to fully dissolve the organic acid aqueous solution in toluene and form a solution; cellulose and concentrated sulfuric acid are added to the system and stirred at 50-80°C, preferably 50°C, for 2-4 hours, preferably 2 hours, to complete the esterification reaction of cellulose; after the esterification reaction is completed, the system is neutralized with an alkaline substance.
[0032] In this invention, cellulose can be sourced from a wide range of sources. To ensure the effectiveness of the reaction, microcrystalline cellulose with a purity of 90% or higher, and more preferably 99% or higher, is preferred as the raw material for the cellulose participating in the reaction. This invention prefers the aforementioned microcrystalline cellulose because, compared to other celluloses, its natural polymeric structural advantages can be fully utilized by the organosilicon rubber material.
[0033] After obtaining the cellulose esterified derivative, according to this invention, the cellulose esterified derivative is reacted with alumina to obtain cellulose esterified derivative-modified alumina. Generally, surface modification of alumina powder usually requires utilizing the surface hydroxyl groups to chemically react with the groups in the modifier or form an entangled structure, thereby forming an organic molecular layer on its surface and increasing its oleophilicity. In this invention, the cellulose esterified derivative is used as a surface modifier for alumina. Under heating and high-speed stirring conditions, the cellulose esterified derivative can complete a grafting reaction with the hydroxyl groups on the powder surface, thereby forming a polymer layer on the alumina surface and increasing the interfacial compatibility between the inorganic alumina powder and the organic resin.
[0034] In this invention, the alumina powder used has a particle size between 20 and 70 μm, such as 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, or 70 μm, and more preferably 40 μm. This is because, within the above particle size range, alumina can be used as a conventional thermally conductive filler.
[0035] In some embodiments of the present invention, the mass ratio of cellulose to alumina is 1:(1.0~2.5), such as 1.0:1.0, 1.0:1.5, 1.0:2.0 or 1.0:2.5, etc.
[0036] This invention also provides a method for preparing the above-mentioned cellulose esterification derivative modified alumina, comprising the following steps:
[0037] S1: Reaction of cellulose with organic acid solution yields cellulose esterification derivatives;
[0038] S2: Mix and react cellulose esterified derivatives with alumina to obtain cellulose esterified derivative modified alumina.
[0039] In this invention, the reaction described in step S1 is carried out under stirring conditions, the reaction temperature is 50~80℃, such as 50℃, 55℃, 60℃, 65℃, 70℃, 75℃ or 80℃, etc., and the reaction time is 2~4 h, such as 2 h, 2.5 h, 3 h, 3.5 h or 4 h, etc.
[0040] In this invention, the reaction described in step S2 is carried out under stirring conditions, the reaction temperature is 50~80℃, such as 50℃, 55℃, 60℃, 65℃, 70℃, 75℃ or 80℃, etc., and the reaction time is 2~10 h, such as 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h or 10 h, etc.
[0041] In some preferred embodiments of the present invention, the method for preparing the cellulose esterified derivative modified alumina includes the following steps:
[0042] (1) Add a certain amount of organic acid aqueous solution to toluene and heat at 40~60℃, preferably 50℃ for 1~3 h to fully dissolve the organic acid aqueous solution in toluene and form a solution; add cellulose and concentrated sulfuric acid to the system and stir at 50~80℃, preferably 50℃ for 2~4 h, preferably 2 h, to complete the esterification reaction of cellulose. After the esterification reaction is completed, neutralize with an alkaline substance to obtain cellulose esterification derivative;
[0043] (2) Under stirring conditions, the alumina powder to be modified is added to the mixture of cellulose esterification derivatives, and the reaction is continued under heating conditions. The reaction temperature is 50~80℃ and the stirring time is 2~10 h.
[0044] (3) The mixed solution was cooled, centrifuged, washed and dried to obtain cellulose esterified derivative modified alumina.
[0045] As can be seen, the preparation method of the above-mentioned cellulose esterification derivative modified alumina provided by the present invention is simple and convenient, requires no complicated instruments and equipment, and is easy to realize industrialization or commercialization.
[0046] The present invention also provides an application of the above-mentioned cellulose esterification derivative modified alumina in organosilicon rubber compounds.
[0047] Furthermore, the present invention also provides an organosilicon rubber compound, wherein the above-mentioned cellulose esterification derivative is modified alumina, organosilicon resin and additives are present.
[0048] The cellulose esterified derivative modified alumina accounts for 30-70% of the silicone rubber compound, such as 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, or 70%.
[0049] Exemplary, in some embodiments of the present invention, 20 parts by weight of the cellulose esterified derivative modified alumina obtained above are weighed, and 35 parts of vinyl silicone oil, 5 parts of fumed silica, 25 parts of ordinary alumina powder filler, 5 parts of crosslinking agent, 0.2 parts of siloxane coupling agent, 0.05 parts of inhibitor, and 0.2 parts of platinum catalyst are added in portions. The mixture is stirred and mixed in a vacuum degassing mixer at 600 r / min for 30 min to obtain the organosilicon rubber compound of cellulose esterified derivative modified alumina.
[0050] The dosage, time, and rate of the specific components mentioned above can be adjusted by those skilled in the art as needed, and will not be elaborated further here.
[0051] Tests have shown that, compared with cellulose-modified alumina, the use of cellulose esterification derivatives to modify alumina in the preparation of silicone rubber compounds can significantly improve the shear strength, tensile strength, and elongation at break of the silicone rubber compounds.
[0052] To further illustrate the present invention, the following examples provide a detailed description. The experimental materials used in the following examples are commercially available products. The purity of the microcrystalline cellulose is above 90%.
[0053] Example 1
[0054] The preparation method of the potting compound of the present invention uses the following raw materials: glacial acetic acid aqueous solution; toluene; concentrated sulfuric acid; sodium carbonate; microcrystalline cellulose (trade name: cellulose powder, hereinafter the same); alumina powder; vinyl silicone oil with a viscosity of 1000 mPa·s and a vinyl content of 1%; a catalyst, which is a 2000 ppm platinum catalyst (hereinafter referred to as platinum catalyst); a crosslinking agent, a hydrogen-containing silicone oil containing more than 3 Si-H bonds with a viscosity of 200 mPa·s and a hydrogen content of 0.36 wt% (hereinafter referred to as crosslinking agent); and an inhibitor, which is 2-methyl-3-butyn-2-ol (hereinafter referred to as alkynol inhibitor). Specifically, it includes the following steps:
[0055] 100 g of a 60% (w / w) aqueous solution of glacial acetic acid was added to 400 mL of toluene and heated at 50 °C for 1 h to fully dissolve the acetic acid in the toluene and form a solution. 10 g of microcrystalline cellulose and 1 g of concentrated sulfuric acid were added to the system and reacted at 50 °C for 2 h to induce cellulose esterification. After esterification, the mixture was neutralized with 1.5 g of sodium carbonate. Then, 100 g of alumina powder with a particle size of 40 μm was added to the mixed solution and reacted at 50 °C for 5 h to chemically modify the alumina. After cooling the resulting mixed solution to room temperature, the liquid was filtered, centrifuged (3000 r / min, 10 min), washed twice with toluene, and dried to obtain cellulose ester-modified alumina powder. The washing liquid and filtrate were collected, filtered, separated, stored, and recycled for reuse.
[0056] Weigh 20 parts by weight of the cellulose ester modified alumina powder obtained above, add 35 parts of vinyl silicone oil, 5 parts of fumed silica, 25 parts of ordinary alumina powder filler, 5 parts of crosslinking agent, 0.05 parts of inhibitor, and 0.2 parts of platinum catalyst in batches, and stir and mix in a vacuum degassing mixer at 600 r / min for 30 min to obtain the organosilicon rubber compound of cellulose ester modified alumina.
[0057] Example 2
[0058] The preparation method of the potting compound of the present invention uses the following raw materials: glacial acetic acid aqueous solution; toluene; concentrated sulfuric acid; sodium carbonate; microcrystalline cellulose; alumina powder; vinyl silicone oil with a viscosity of 1000 mPa·s and a vinyl content of 1%; a catalyst, which is a 2000 ppm platinum catalyst; a crosslinking agent, a hydrogen-containing silicone oil containing more than 3 Si-H bonds with a viscosity of 200 mPa·s and a hydrogen content of 0.36 wt%; a silane coupling agent, which is glycidoxypropyltrimethoxysilane; and an inhibitor, which is 2-methyl-3-butyn-2-ol. Specifically, the method includes the following steps:
[0059] 100 g of a 60% (w / w) aqueous solution of glacial acetic acid was added to 400 mL of toluene and heated at 50 °C for 1 h to fully dissolve the acetic acid in the toluene and form a solution. 10 g of microcrystalline cellulose and 1 g of concentrated sulfuric acid were added to the system and reacted at 50 °C for 2 h to induce cellulose esterification. After the reaction was complete, the mixture was neutralized with 1.5 g of sodium carbonate. Then, 60 g of alumina powder with a particle size of 70 μm was added to the mixed solution and reacted at 50 °C for 5 h to chemically modify the alumina. After cooling the resulting mixed solution to room temperature, the liquid was filtered, centrifuged (3000 r / min, 10 min), washed twice with toluene, and dried to obtain cellulose ester-modified alumina powder. The washing liquid and filtrate were collected, filtered, separated, stored, and recycled for reuse.
[0060] Weigh 20 parts by weight of the cellulose ester modified alumina powder obtained above, add 35 parts of vinyl silicone oil, 5 parts of fumed silica, 25 parts of ordinary alumina powder filler, 5 parts of crosslinking agent, 0.4 parts of silane coupling agent, 0.05 parts of inhibitor, and 0.2 parts of platinum catalyst in batches, and stir and mix in a vacuum degassing mixer at 600 r / min for 30 min to obtain the organosilicon rubber compound of cellulose ester modified alumina.
[0061] Example 3
[0062] The preparation method of the potting compound of the present invention uses the following raw materials: glacial acetic acid aqueous solution; toluene; concentrated sulfuric acid; sodium carbonate; microcrystalline cellulose; alumina powder; vinyl silicone oil with a viscosity of 1000 mPa·s and a vinyl content of 1%; a catalyst, which is a 2000 ppm platinum catalyst; a crosslinking agent, a hydrogen-containing silicone oil containing more than 3 Si-H bonds with a viscosity of 200 mPa·s and a hydrogen content of 0.36 wt%; a silane coupling agent, which is glycidoxypropyltrimethoxysilane; and an inhibitor, which is 2-methyl-3-butyn-2-ol. Specifically, the method includes the following steps:
[0063] 100 g of a 60% (w / w) aqueous solution of glacial acetic acid was added to 400 mL of toluene and heated at 50 °C for 1 h to fully dissolve the acetic acid in the toluene and form a solution. 10 g of microcrystalline cellulose and 1 g of concentrated sulfuric acid were added to the system and reacted at 50 °C for 2 h to induce cellulose esterification. After the reaction was complete, the mixture was neutralized with 1.5 g of sodium carbonate. Then, 80 g of alumina powder with a particle size of 20 μm was added to the mixed solution and reacted at 50 °C for 5 h to chemically modify the alumina. After cooling the resulting mixed solution to room temperature, the liquid was filtered, centrifuged (3000 r / min, 10 min), washed twice with toluene solvent, and dried to obtain cellulose ester-modified alumina powder. The washing liquid and filtrate were collected, filtered, separated, stored, and recycled for reuse.
[0064] Weigh 20 parts by weight of the cellulose ester modified alumina powder obtained above, add 35 parts of vinyl silicone oil, 5 parts of fumed silica, 25 parts of ordinary alumina powder filler, 5 parts of crosslinking agent, 0.8 parts of silane coupling agent, 0.05 parts of inhibitor, and 0.2 parts of platinum catalyst in batches, and stir and mix in a vacuum degassing mixer at 600 r / min for 30 min to obtain the organosilicon rubber compound of cellulose ester modified alumina.
[0065] Comparative Example 1
[0066] The preparation method of the potting compound of the present invention uses the following raw materials: glacial acetic acid aqueous solution; toluene; microcrystalline cellulose; alumina powder; vinyl silicone oil with a viscosity of 1000 mPa·s and a vinyl content of 1%; a catalyst, which is a 2000 ppm platinum catalyst; a crosslinking agent, a hydrogen-containing silicone oil containing more than 3 Si-H bonds with a viscosity of 200 mPa·s and a hydrogen content of 0.36 wt%; a silane coupling agent, which is glycidoxypropyltrimethoxysilane; and an inhibitor, which is 2-methyl-3-butyn-2-ol. Specifically, it includes the following steps:
[0067] 100 g of water was added to 400 mL of toluene and heated at 50 °C for 1 h with stirring to form a toluene solution. 10 g of microcrystalline cellulose and 100 g of alumina powder with a particle size of 40 μm were added to the mixed solution, and the mixture was reacted at 50 °C for 5 h. After cooling the resulting mixed solution to room temperature, the liquid substance was filtered, centrifuged (3000 r / min, 10 min), washed twice with toluene solvent, and then dried to obtain cellulose-modified alumina powder. The washing liquid and filtrate can be collected, filtered, separated, stored, and recycled for reuse.
[0068] Weigh 20 parts by weight of the cellulose-modified alumina powder obtained above, add 35 parts of vinyl silicone oil, 5 parts of fumed silica, 25 parts of ordinary alumina powder filler, 5 parts of crosslinking agent, 0.2 parts of silane coupling agent, 0.05 parts of inhibitor, and 0.2 parts of platinum catalyst in batches, and stir and mix in a vacuum degassing mixer at 600 r / min for 30 min to obtain the organosilicon rubber compound of cellulose-modified alumina.
[0069] Comparative Example 2
[0070] The preparation method of the potting compound of the present invention uses the following raw materials: glacial acetic acid aqueous solution; toluene; alumina powder; vinyl silicone oil with a viscosity of 1000 mPa·s and a vinyl content of 1%; a catalyst, which is a 2000 ppm platinum catalyst; a crosslinking agent, a hydrogen-containing silicone oil containing more than 3 Si-H bonds with a viscosity of 200 mPa·s and a hydrogen content of 0.36 wt%; a silane coupling agent, which is glycidoxypropyltrimethoxysilane; and an inhibitor, which is 2-methyl-3-butyn-2-ol. Specifically, the method includes the following steps:
[0071] 100 g of a 60% (w / w) aqueous solution of glacial acetic acid was added to 400 mL of toluene and heated at 50 °C for 1 h to ensure complete dissolution of the acetic acid solution in the toluene. 60 g of alumina powder with a particle size of 70 μm was added to the solution and reacted at 50 °C for 5 h to chemically modify the alumina. After cooling the resulting solution to room temperature, the liquid was filtered, centrifuged (3000 r / min, 10 min), washed twice with toluene, and dried to obtain the modified alumina powder. The washing liquid and filtrate were collected, filtered, separated, stored, and recycled for reuse.
[0072] Weigh 20 parts by weight of the modified alumina powder obtained above, add 35 parts of vinyl silicone oil, 5 parts of fumed silica, 25 parts of ordinary alumina powder filler, 5 parts of crosslinking agent, 0.4 parts of silane coupling agent, 0.05 parts of inhibitor, and 0.2 parts of platinum catalyst in batches, and stir and mix in a vacuum degassing mixer at 600 r / min for 30 min to obtain the alumina silicone rubber compound.
[0073] Comparative Example 3
[0074] The preparation method of the potting compound of the present invention uses the following raw materials: glacial acetic acid aqueous solution; toluene; concentrated sulfuric acid; sodium carbonate; microcrystalline cellulose; alumina powder; vinyl silicone oil with a viscosity of 1000 mPa·s and a vinyl content of 1%; a catalyst, which is a 2000 ppm platinum catalyst; a crosslinking agent, a hydrogen-containing silicone oil containing more than 3 Si-H bonds with a viscosity of 200 mPa·s and a hydrogen content of 0.36 wt%; a silane coupling agent, which is glycidoxypropyltrimethoxysilane; and an inhibitor, which is 2-methyl-3-butyn-2-ol. Specifically, the method includes the following steps:
[0075] 100 g of a 60% (w / w) aqueous solution of glacial acetic acid was added to 400 mL of toluene and heated at 50 °C for 1 h to fully dissolve the acetic acid in the toluene and form a solution. 1 g of microcrystalline cellulose and 1 g of concentrated sulfuric acid were added to the system and reacted at 50 °C for 2 h to induce cellulose esterification. After the reaction was complete, the mixture was neutralized with 1.5 g of sodium carbonate. Then, 80 g of alumina powder with a particle size of 20 μm was added to the mixed solution and reacted at 50 °C for 5 h to chemically modify the alumina. After cooling the resulting mixed solution to room temperature, the liquid was filtered, centrifuged (3000 r / min, 10 min), washed twice with toluene, and dried to obtain cellulose ester-modified alumina powder. The washing liquid and filtrate were collected, filtered, separated, stored, and recycled for reuse.
[0076] Weigh 20 parts by weight of the cellulose ester modified alumina powder obtained above, add 35 parts of vinyl silicone oil, 5 parts of fumed silica, 25 parts of ordinary alumina powder filler, 5 parts of crosslinking agent, 0.8 parts of silane coupling agent, 0.05 parts of inhibitor, and 0.2 parts of platinum catalyst in batches, and stir and mix in a vacuum degassing mixer at 600 r / min for 30 min to obtain the organosilicon rubber compound of cellulose ester modified alumina.
[0077] Performance testing
[0078] The adhesives prepared in Examples 1-3 were subjected to viscosity (cps, according to GB / T 10247-2008) tests. Anodized aluminum was selected as the substrate, and the test specimens were dumbbell-shaped (2.0±0.2 mm thick, 6 mm wide) adhesive strips conforming to national standards. After curing at 120℃ for 1 h, the shear strength (MPa, according to G / T 7124-2008), tensile strength (MPa, according to GB / T 528-2009), and elongation at break (%, according to GB / T 528-2009) were tested. Simultaneously, the adhesives obtained in Comparative Examples 1-3 were tested using the same method.
[0079] The test results are shown in Table 1:
[0080] Table 1
[0081]
[0082] As shown in Table 1, compared to Comparative Example 1, when cellulose was not used as a solution in the continuous modification reaction of alumina, the actual modification effect of cellulose on the powder was significantly reduced in Example 1. The viscosity of the colloid using fully modified powder in Example 1 was slightly higher than that in Comparative Example 1, while its shear strength, tensile strength, and elongation at break were significantly improved. Compared to Comparative Example 2, which did not use cellulose to modify alumina at all, Example 2 had a significantly higher viscosity and a more significant performance enhancement, with mechanical properties far superior to the colloid system without modified powder. Comparative Example 3 reduced the amount of cellulose added during the reaction. Compared to Example 3 with sufficient cellulose addition, its shear strength, tensile strength, and elongation were enhanced compared to the colloid without modified powder (such as Comparative Examples 1 and 2), but the actual performance was slightly lower than that of Example 3.
[0083] In the examples and comparative examples, as the amount of siloxane coupling agent added to the formulation components increased, the shear strength, tensile strength and elongation of the rubber compound gradually improved. Among them, the performance of the rubber compound using cellulose ester modified alumina powder as filler was significantly better than that of the rubber compound using original alumina powder and incompletely modified alumina powder when using low and high content coupling agent. However, with the use of high content siloxane coupling agent, its effect on improving the performance of the rubber compound decreased.
[0084] In summary, this invention selects cellulose esterified derivatives as the surface modification material for alumina powder. This material is widely available, low in cost, and its pretreatment and modification processes are simple. After surface modification of alumina powder, its basic anti-settling properties and toughness reinforcement properties are significantly improved. Furthermore, the natural polymer structure of organic cellulose can enhance interfacial adhesion. Using cellulose esterified derivatives to modify alumina as a filler to prepare organosilicon rubber compounds can effectively improve the material's adhesion, as well as its mechanical properties, thermal stability, etc., further expanding the material's application scope. Compared to existing modified materials, cellulose is environmentally friendly, better meeting the demands of modern industry for environmental protection and sustainable development.
[0085] The above description of the disclosed embodiments enables those skilled in the art to make or use the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A cellulose esterified derivative modified alumina, characterized in that, It is obtained by reacting cellulose esterification derivatives with alumina; The cellulose esterification derivative is obtained by reacting cellulose with an organic acid solution; the cellulose is selected from microcrystalline cellulose; the organic acid solution is a 50-70% by mass aqueous solution of an organic acid; the organic acid in the organic acid solution is selected from any one or more of formic acid, acetic acid, or propionic acid. The mass ratio of cellulose to alumina is 1:(1.0~2.5).
2. The cellulose esterified derivative modified alumina according to claim 1, characterized in that, The ratio of cellulose to organic acid solution is 1 g:(40~60) mL.
3. The cellulose esterified derivative modified alumina according to claim 1 or 2, characterized in that, The purity of the microcrystalline cellulose is above 90%.
4. The cellulose esterified derivative modified alumina according to claim 1, characterized in that, The alumina has a medium particle size of 20~70 μm.
5. A method for preparing cellulose esterified derivative modified alumina according to any one of claims 1 to 4, characterized in that, Includes the following steps: S1: Reaction of cellulose with organic acid solution yields cellulose esterification derivatives; S2: Mix and react cellulose esterified derivatives with alumina to obtain cellulose esterified derivative modified alumina.
6. The preparation method according to claim 5, characterized in that, The reaction described in step S1 is carried out under stirring conditions, at a temperature of 50-80°C, and for a time of 2-4 hours. The reaction described in step S2 is carried out under stirring conditions, at a temperature of 50~80℃, and for a time of 2~10 h. The reaction described in step S1 is carried out in the presence of concentrated sulfuric acid; After the reaction described in step S1 is completed, an alkaline substance is used for neutralization, wherein the alkaline substance is selected from sodium carbonate and / or potassium carbonate.
7. The application of the cellulose esterified derivative modified alumina according to any one of claims 1 to 4, or the cellulose esterified derivative modified alumina prepared according to the preparation method according to claim 5 or 6, in organosilicon rubber compounds.
8. An organosilicon rubber compound, characterized in that, It includes cellulose esterified derivative modified alumina according to any one of claims 1 to 4 or cellulose esterified derivative modified alumina prepared according to the preparation method according to claim 5 or 6, silicone oil, and additives.
9. The silicone rubber compound according to claim 8, characterized in that, The cellulose esterified derivative modified alumina accounts for 30-70 wt% of the organosilicon rubber compound.
Citation Information
Patent Citations
Method for realizing cellulose surface esterification in aqueous solution
CN117209614A
Cellulose modified aluminum oxide / epoxy resin material as well as preparation method and application thereof
CN118791837A